1988
DOI: 10.1080/08873267.1988.9976830
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic psychology and introductory textbooks.

Abstract: The introductory psychology textbook is the first place one might look to assess the "impact" of a particular school or approach on the development of psychology as a whole. In fact, the impact of the humanistic movement on psychology as an academic institution might be operationally defined as its representation in introductory texts. After all, notwithstanding the particular biases of an author, these introductory texts are generally aimed at giving well balanced, comprehensive coverage of the field at large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…But no investigation into humanistic psychology's representation in introductory textbooks has occurred since Churchill's (1988) analysis. Systematically reviewing the contents of 13 recently published texts, Churchill found that the humanistic approach was relegated mostly to chapters on personality and therapy (with little discussion elsewhere) and that the coverage in these areas was generally minimal (rarely more than one to two pages).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But no investigation into humanistic psychology's representation in introductory textbooks has occurred since Churchill's (1988) analysis. Systematically reviewing the contents of 13 recently published texts, Churchill found that the humanistic approach was relegated mostly to chapters on personality and therapy (with little discussion elsewhere) and that the coverage in these areas was generally minimal (rarely more than one to two pages).…”
mentioning
confidence: 99%
“…During the time spanning the surveys by Churchill (1988), Wertz (1992Wertz ( , 1998, and Kumar (2015), the distance from humanistic psychology's origins and founders has increased, and assessments of its historical legacy have been conducted (e.g., Schneider, Bugental, & Pierson, 2001). New figures, ideas, and applications have been introduced, and its uncertain relationship with the emerging positive psychology movement has been debated (e.g., Robbins, 2008;Seligman & Csikszentmihalyi, 2000;Waterman, 2013).…”
mentioning
confidence: 99%
“…The purpose is neither to review nor to criticize Harlow's work but to use it as a case example of how stressful research is presented to the beginning student. Indirectly, this analysis should cast light on the beliefs and culture of animal research through its strategy of presenting a research topic at the elementary level, much as Churchill (1988) and Massey (1988) have analyzed the presentation of humanistic psychology in general textbooks.…”
Section: Harlow's Monkeys In College Textbooksmentioning
confidence: 99%
“…Since about 1975, the most prominent manifestation of these roots-the humanistic psychology movement 2 -has been relegated to a quaint afterthought in the curriculum of most APA-accredited doctoral programs in psychology (Giorgi, 1987;Mayne, Norcross, & Sayette, 1994;Wertz, 1992). At the undergraduate level, humanistic psychology receives slightly more acknowledgement, but mainly with regard to the work of Abraham Maslow and Carl Rogers and not the more philosophically inclined existential-humanistic thinkers such as Rollo May, R. D. Laing, Ernest Becker, and James Bugental (Churchill, 1988).…”
mentioning
confidence: 99%